Determination of the complete mitochondrial genome sequence of mussel Cristaria plicata (Leach). (3rd March 2016) - Wang, Heng; He, Liping; Yang, Xiaoxue; Yang, Shoubao; Li, Chen; Wang, Xiarong
Abstract: In the present study, the total mitochondrial genome of a freshwater mussel Cristaria plicata (Leach) was sequenced and determined. The mitogenome is 15, 710 bp in length. It consists of 13 protein-coding genes, 22 tRNA genes and 2 rRNA genes. The total base composition is: 36.49% A, 27.23% T, 23.21% C, and 13.07% G with an A+T rich feature (63.72%). These results provide useful data to study of the genetics, systematics and conservation of mussel C. plicata (Leach).